The impact of peer personality on academic achievement - Bart H. H. Golsteyn; Jan Adrianus Non; Ulf Zölitz (University of Zurich, Department of Economics, 2017)
This paper provides evidence of a novel facet of peer effects by showing how peer personality affects educational achievement. We exploit random assignment of students to university sections and find that students perform better in the presence of more persistent peers and more risk-averse peers. In particular, low-persistence students benefit from highly-persistent peers without devoting additional efforts to studying. However, highly-persistent students are not affected by the persistence of their peers. The personality peer effects that we document are distinct from other observable peer characteristics and suggest that the personality traits of peers causally affect human capital accumulation.
Keywords: I21; I24; J24; 330; Personality; peer effects; non-cognitive skills